In Silico Modelling and Docking Simulation of EGFR-Targeted Diphtheria Toxin Chimera with Various Targeting Moieties - Afif Naufal, Muhammad, BMed; Ansell Susanto, Benedictus, BMed; Gunawan, Talitha Dinda, BMed; Ridha Lukman, Azhar, BMed; Rizqina, Alifa Rahma, BMed; Misbahul Fuad, Muhammad, BMed (UI Scholars Hub, 2024)
Introduction: Cancer is a major etiology of death worldwide due to high mortality and suboptimal medicine. However, an emerging field, targeted therapy enabled a more selective and effective therapeutic action. This article aims to analyze in-silico the hypothetical targeted therapy agent that is combinations of conjugate consisting of EGFR targeting moieties and diphtheria toxin (DT-390). Method: Our novel peptide is a conjugate of a novel EGFR targeting peptide and DT-390, forming a chimera. The tertiary structure was predicted using AlphaFold 2.0. The best IDDT scoring and stereochemistry profiles were utilized. The HADDOCK2.4 webserver modelled the docking between our model and EGFR dimers, limited to its active residues. Gibbs free energy analysis, dissociation constants, and interfacial contacts are the primary outcomes measured. Results: The confidence of the models ranged from moderate to high. The model conjugated with native hEGF (ΔG -14 kcal/mol) provided the best confidence compared to our novel peptide (ΔG -12.8 kcal/mol). Higher valences of peptides were found to have better confidences (hEGF ΔG -19.3 kcal/mol; EGFR de novo ΔG -14.3 kcal/mol). Our findings correspond to an in vitro study by Qi et al that concludes a bivalent hEGF is more effective than monovalent. However, the linker used also displays considerable bonding to the target. This may be from the linker’s considerable flexibility that allows it to accidentally interact with EGFR active residues. It is to be noted that the interactions formed were nonspecific and therefore unlikely to cause off-target effects. Conclusion: Our novel EGFR targeting peptide is effective in increasing selectivity of DT-390 to EGFR active residues. Our study does not consider the structural changes that might occur due to erroneous binding to other receptors. Further docking and molecular dynamics studies are important to further develop this novel system as a targeted therapy agent.